2022
DOI: 10.1155/2022/3383773
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Characteristics of the Seepage Erosion Process in Porous Soil

Abstract: Seepage-induced erosion in porous soil has always been a major concern in the field of geofluids. Various fractal models have been built to theoretically investigate the porosity and permeability coefficient. However, the seepage erosion process (i.e., incubation, formation, evolution, and destruction) in porous soil is not clearly demonstrated to clarify the seepage fractal characteristics. In this paper, a series of hydraulic tests were performed to reveal the mass fractal characteristics of sandy gravels, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Soil particles were classified in descending order of particle size as sand (0.05~2 mm), silt (0.002~0.05 mm), and clay (<0.002 mm). Then, D m (soil mass fractal dimension) can be estimated [28]:…”
Section: Soil Particle Composition and Mass Fractal Dimensionmentioning
confidence: 99%
“…Soil particles were classified in descending order of particle size as sand (0.05~2 mm), silt (0.002~0.05 mm), and clay (<0.002 mm). Then, D m (soil mass fractal dimension) can be estimated [28]:…”
Section: Soil Particle Composition and Mass Fractal Dimensionmentioning
confidence: 99%
“…For example, in the third seepage, the volume of pores with a size of pores greater than 3.0 mm decreases by 73.316%, and these pores are further transformed into small pores. In this stage, the seepage mode belongs to the mixture flow (preferential piston flow), and both flow patterns exist simultaneously, resulting in a complex change of the soil structure under continuous seepage erosion [91].…”
Section: Evidence For the Seepage Evolution Modelmentioning
confidence: 99%
“…Based on the change in the microstructural arrangement of soil particles, the microscopic change in the permeability coefficient of soil is studied experimentally [45][46][47]. The coupling equation of seepage and erosion shows that the pore water pressure in soil increases until the hydraulic gradient is greater than the critical hydraulic gradient, and the fine particle phase migrates and loosens from the soil, resulting in deformation and instability [48][49][50][51]. Research on bank-slope stability has shown that numerical analysis methods provide an appropriate and effective tool to establish numerical models.…”
Section: Introductionmentioning
confidence: 99%